EFFECT OF CONVECTIVE BOUNDARY CONDITIONS AT BOTTOM WALL ON NATURAL CONVECTIONS IN A SQUARE CAVITY - ASWATHA (Journal of Engineering Science and Technology, 2013)
Simulations were carried out for natural convection in a square cavity using finite volume based computational procedure with biased quadratic elements to investigate the influence of convective boundary conditions at bottom wall. Parametric study has been carried out for a wide range of Rayleigh number (Ra) (103 ≤ Ra ≤ 108), Prandtl number (Pr) (0.7 ≤ Pr ≤ 17) and heat transfer coefficient (h) (0.1 ≤ h ≤ 104 W/m2 K). It is observed from the present study that the heat transfer is primarily due to conduction for Rayleigh number up to 104. Convection dominant heat transfer is observed at higher Ra values. The intensity of circulation increases with increase in Ra number. The average heat transfer rate at the bottom wall is found to be invariant for all values of heat transfer coefficient for Ra up to 104. The power law correlations between average Nusselt number and Rayleigh numbers are presented for convection dominated regimes.